(untitled) (Scientific Researches in Academia, 2024)
This study explores how English language teachers (ELTs) have improved their students’ speaking abilities in the context of Nepal. With the rapid pace at which the world is changing and the emphasis on communication, especially in English, students encounter a number of obstacles in their efforts to improve their speaking skills. Drawing upon qualitative methodology, interviews were carried out with two ELTs from the Kathmandu Valley to find out their viewpoints on teaching strategies, learning environments, and approaches to addressing learner challenges. The results show that there are a number of important obstacles, including speaking nervousness, a lack of learning opportunities, and gaps in knowledge between theory and practice. By highlighting interactive teaching techniques and student-centered approaches, both participants emphasize the crucial part that teachers play in creating inclusive and encouraging learning environments. In order to enhance equitable access to high-quality education, the study urges on stakeholders to address systemic issues and support a holistic approach to learning languages. Overall, this study shed light on the difficulties involved in teaching languages and highlights how important it is for teachers to support their students’ confidence and speaking ability in the language.